Маленький принц: сказка : на рус. и фр. яз. / А. Сент-Экзюпери - Сент-Экзюпери Антуан (Международные отношения, 1992)
Экземпляры: Ф. 4 (20210518) / Инвентарный номер: 31035 / Цена: / Сис.шифр: 81.2Фр / Авт.знак: С 31 / ГРНТИ: 17.82 / ББК: 81.2Фр + 84(4Фра)